2007
DOI: 10.1111/j.1365-2958.2007.05787.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective killing of the human pathogen Candida albicans by a specific inhibitor of non‐essential mitotic kinesin Kip1p

Abstract: SummaryKinesins from the bipolar (Kinesin-5) family are conserved in eukaryotic organisms and play critical roles during the earliest stages of mitosis to mediate spindle pole body separation and formation of a bipolar mitotic spindle. To date, genes encoding bipolar kinesins have been reported to be essential in all organisms studied. We report the characterization of CaKip1p, the sole member of this family in the human pathogenic yeast Candida albicans. C. albicans Kip1p appears to localize to the mitotic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…It is possible that blebbistatin treatment traps myosin II on a fraction of SCVs/ Sifs, preventing its release by blocking its ATPase activity. A similar trapping of microtubule motors on their respective cytoskeletal filaments/cargo using specific drugs or nonhydrolyzable ATP analogues has been reported (9,14). The observation that myosin II can associate with SCVs/Sifs (albeit under artificial conditions) suggests that this motor acts locally at this compartment during infection.…”
Section: Discussionmentioning
confidence: 85%
“…It is possible that blebbistatin treatment traps myosin II on a fraction of SCVs/ Sifs, preventing its release by blocking its ATPase activity. A similar trapping of microtubule motors on their respective cytoskeletal filaments/cargo using specific drugs or nonhydrolyzable ATP analogues has been reported (9,14). The observation that myosin II can associate with SCVs/Sifs (albeit under artificial conditions) suggests that this motor acts locally at this compartment during infection.…”
Section: Discussionmentioning
confidence: 85%
“…Kip1p was also inhibited by an aminobenzothiazole compound, which caused Kip1p to bind to microtubules in a rigor-like mechanism resulting in cell death. These studies reveal that drugs that target nonessential components of the microtubule apparatus can produce fungicidal effects, presumably due to arrest of the mitotic spindle, and thus are effective antifungal agents (14). It remains to be seen if similar studies of other kinesins, including Kar3p, will provide additional targets for antifungal drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…(63). In addition, Chua et al investigated the role of the kinesin Kip1p in C. albicans and showed that loss of Kip1p led to aberrant rounds of spindle pole body duplication, again accompanied by mitotic delay and elongated growth (14). Kip1p was also inhibited by an aminobenzothiazole compound, which caused Kip1p to bind to microtubules in a rigor-like mechanism resulting in cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all of these morphological states, microtubuleassociated motor proteins play major roles in microtubule cytoskeleton remodeling, nuclear movements, chromosome segregation, and cargo transport (7)(8)(9). This provides a rationale for their use as novel targets for antifungal drugs (10).…”
mentioning
confidence: 99%